The Volcano Simulation Software Implementation in Integrated Physics Learning Disaster Mitigation to Develop Critical Thinking Skills - Desinta Ramadhani Pratiwi; Eko Hariyono (IKIP Mataram, 2022)
This research aimed to analyze the students’ learning results in the critical thinking skills using volcano simulation software. In addition, students’ response to the volcano software integration into physics learning is also described in the current research. The research samples are students of SMA Tamansiswa Mojokerto consisting of two classes, namely XI MIPA 1 and XI MIPA 2, with 65 students. This research is included in quantitative research by using One Group Pretest – Posttest Design. The pre-test was given first, and at the end of the learning, the samples were given a post-test. The data collection instruments used in this research are the critical thinking ability test and student response questionnaire sheet. The data were analyzed descriptively (n-gain) and statistically (t-test). The results showed (1) an increase in the critical thinking skills with an average score of n-gain of 0,87 and 0,83 with the high criteria and (2) there is no difference in the average score of n-gain between both classes (p > 0.05). It can be concluded that physics learning by using volcano simulation software effectively increases the students’ learning results and critical thinking skills. The average percentage of students’ responses is 82% with a very good category. The use of volcano simulation software on the critical thinking skills obtained results that it being more interesting and easier for students to understand better the taught concepts as well as can practice the critical thinking skills of students.